Study on the Outer Radiation Belt Location in the 23–24 Solar Cycles - Dmitriev, Alexei V. (Challenging Issues on Environment and Earth Science Vol. 6, 2021)
Within the last two solar cycles (from 2001 to 2020), the location of the outer radiation belt (ORB) was determined using NOAA/Polar-orbiting Operational Environmental Satellite observations of energetic electrons with energies above 30 keV. It was found that the ORB was shifted a little (~1 degrees) in the European and North American sectors while in the Siberian sector, ORB was displaced equatorward by more than 3 degrees. The displacements corresponded qualitatively to the change of geomagnetic field predicted by the IGRF-12 model. However in the Siberian sector, the model has a tendency to underestimate the equatorward shift of ORB. The shift became prominent after 2012 that might be related to a geomagnetic jerk occurred in 2012 – 2013. The displacement of ORB to lower latitudes in the Siberian sector can contribute to an increase in the occurrence rate of mid-latitude auroras observed in the Eastern Hemisphere.